Revision of the subgenus Stigmatodipogon Ishikawa of the genus Dipogon Fox (Hymenoptera: Pompilidae: Pepsinae) - Shimizu, Akira; Lelej, Arkady S.; Loktionov, Valery M.; Nishimoto, Yutaka; Endo, Tomoji (Zootaxa, 2018)
The systematics of the subgenus Stigmatodipogon Ishikawa of the genus Dipogon Fox is revised. Six species are listed. Two new species, Dipogon (Stigmatodipogon) kurokawai Shimizu, sp. nov. (Honshu, Japan) and D. (S.) lao Loktionov & Lelej, sp. nov. (Laos) are described and illustrated and other four species from Japan, the Russian Far East and Eastern Siberia are redescribed. A new combination is proposed for D. (S.) budrisi (Loktionov & Lelej, 2014), comb. nov. Nesting records of D. (S.) kurokawai and prey records of D. (S.) macrostigmatus Ishikawa, 1959 and D. (S.) petiolatus Lelej, 1986 are presented. These are the first records of biology for this subgenus. A key to species is provided.